Optical CO2 Gas Sensing Based on TiO2 Thin Films of Diverse Thickness Decorated with Silver Nanoparticles - Muhammad Akram Raza; Anam Habib; Zakia Kanwal; Syed Sajjad Hussain; Muhammad Javaid Iqbal; Murtaza Saleem; Saira Riaz; Shahzad Naseem (Advances in Materials Science and Engineering)
The fabrication, characterization, and CO2 gas detection performance of single component-based and hetero-nanostructure-based optical gas sensors are reported in the present work. Single component-based structures include (i) TiO2 thin films with varied film thickness (37.45 nm, 51.92 nm, and 99.55 nm) fabricated via the RF sputtering system for different deposition times and (ii) silver nanoparticles (AgNPs) deposited on the glass substrate by the wet chemical method. Hetero-nanostructures were achieved by decorating the AgNPs on the predeposited TiO2 thin films. The structural, morphological, and optical characteristics of prepared samples were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), and ellipsometry, respectively. XRD analysis of AgNPs confirmed the crystalline nature of prepared particles with average crystallite size of 21 nm, however, in the case of TiO2 films XRD results suggested amorphous structure of all as-deposited films. size 21 nm. The SEM micrographs confirmed the deposition of AgNPs on the TiO2 thin films. With increasing sputtering time, TiO2 films were found to be denser and more compact, indicating a reduced porosity and higher film thickness. CO2 gas-sensing properties were investigated by measuring the optical transmission spectra in alone air and in CO2 gaseous atmosphere at room temperature. It was observed that neither TiO2 thin films even with higher thickness nor alone AgNPs could demonstrate any substantial gas-sensing activity. Nevertheless, TiO2/AgNP hetero-nanostructured substrates exhibited excellent CO2 gas-sensing performance as indicated by a huge change in the transmission spectra. The enhanced sensing efficiency of TiO2/AgNP nanostructures owing to synergistic effects suggests a promising role of our manufactured sensors in practical applications.